Novel bioceramics from digital light processing of calcite/acrylate blends and low temperature pyrolysis. Issue 10 (July 2020) - Elsayed, Hamada; Picicco, Martiniano; Ferroni, Letizia; Gardin, Chiara; Zavan, Barbara; Bernardo, Enrico
Abstract: Porous bioceramic composites with complex shapes were easily fabricated starting from fine calcite (CaCO3 ) particles (<10 μm) immersed in a liquid photocurable polymer. The building of 3D structures, layer-by-layer, was achieved by means of Digital Light Processing (DLP), using a commercial stereo-lithography 3D printer. The pyrolysis of the hardened photosensitive polymer, in nitrogen atmosphere (at 500 °C), left calcite powders embedded in an amorphous carbon matrix, without any degradation of the main phase, which retained its biocompatibility, according to the cell culture studies. In addition, calcite was successfully converted into hydroxyapatite (HAp), by simple immersion of samples in a phosphatizing bath (aqueous solution of sodium phosphate), for 2 weeks, obtaining HAp-pyrolytic carbon composite scaffolds. The developed structures, after phosphatization, exhibited an adequate strength-to-density ratio (compressive strength of 1.4 MPa with porosity of about 80 vol%).